2022
DOI: 10.1108/dlo-07-2022-0122
|View full text |Cite
|
Sign up to set email alerts
|

Positive affect as a resource and the mediating role of mindfulness on employees during times of disruption

Abstract: Purpose The purpose of this paper is to examine the importance of employee state of mind through the lens of Conservation of Resources Theory, emphasizing the importance of mindfulness for employee productivity. Design/methodology/approach A survey consisting of previously validated instruments was administered to alumni of an MBA program, with 321 responses received from fully employed participants. The relationships among constructs were tested using partial least squares path modeling. Findings The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…According to this theory, individuals possess limited personal resources, including tangible, identity, personal, and energy resources, and they are motivated to acquire, preserve, and maintain these valuable resources. Regarding resources, existing research has indicated a correlation between individuals' positive emotions and productive behaviors [46] and the impact of psychological support [47] and relationships [48] on turnover intention, job satisfaction, and performance. Hobfoll [49] suggests that driven by evolution, humans always strive to obtain, protect, and build these resources, viewing resource loss and its risk as threats.…”
Section: Conservation Of Resources Theorymentioning
confidence: 99%
“…According to this theory, individuals possess limited personal resources, including tangible, identity, personal, and energy resources, and they are motivated to acquire, preserve, and maintain these valuable resources. Regarding resources, existing research has indicated a correlation between individuals' positive emotions and productive behaviors [46] and the impact of psychological support [47] and relationships [48] on turnover intention, job satisfaction, and performance. Hobfoll [49] suggests that driven by evolution, humans always strive to obtain, protect, and build these resources, viewing resource loss and its risk as threats.…”
Section: Conservation Of Resources Theorymentioning
confidence: 99%